Speaking with Care, Thinking with Depth: How Modality Shapes Critical Thinking and Engagement in EFL Learners’ Classroom Interaction - Syam , Nur Ina; Ulfa, Andi Yurni; Room, Fahmi; Riskayadi, Riskayadi; Ibrahim , Muliaty (REiLA : Journal of Research and Innovation in Language, 2025)
Speaking with care and thinking with depth are essential competencies in English as a Foreign Language (EFL) classrooms, yet many learners struggle to balance politeness with assertiveness when contributing to discussions. While modality has been studied as a grammatical feature, its function as a pragmatic tool for shaping critical thinking and sustaining engagement remains underexplored. This qualitative descriptive study investigated how modality is employed by fourth-semester EFL learners at Universitas Muhammadiyah Bulukumba to manage stance, encourage respectful dialogue, and support deeper reasoning in classroom interaction. Data were collected over six weeks through classroom observations and audio recordings of discussion sessions, stimulated recall interviews with seven students, and semi-structured interviews with two lecturers. Thematic analysis revealed that modality served both interpersonal and cognitive purposes: hedging expressions such as maybe and I think reduced the perceived risk of error, encouraged openness to multiple perspectives, and fostered group harmony, while stronger forms such as must and should enhanced clarity and argumentative strength. However, excessive hedging sometimes weakened reasoning and reduced precision. Lecturers emphasized that explicit, context-based instruction, supported by sentence starters and role-play activities, increased learners’ confidence and participation, even among hesitant speakers. These findings position modality as a vital communicative strategy for cultivating critical thinking and inclusive engagement, suggesting that EFL pedagogy should integrate targeted modality training to prepare learners for effective, courteous, and intellectually rich communication in academic and professional settings.